Man for himself - "Fromm, Erich" (London, 2003)
n Man for Himself, Erich Fromm examines the confusion of modern women and men who, because they lack faith in any principle by which life ought to be guided, become the helpless prey forces both within and without. From the broad, interdisciplinary perspective that marks Fromm's distinguished oeuvre, he shows that psychology cannot divorce itself from the problems of philosophy and ethics, and that human nature cannot be understood without understanding the values and moral conflicts that confront us all. He shows that an ethical system can be based on human nature rather than on revelations or traditions. As Fromm asserts, "If man is to have confidence in values, he must know himself and the capacity of his nature for goodness and productiveness."
Keywords: Psychology